Kelayakan Modul Submateri Tumbuhan Paku Kelas X SMA dari Hasil Inventarisasi Pteridophyta Kabupaten Sanggau - Patrisia Vika; Syamswisna Syamswisna; Hayatul Fajri (Florea : Jurnal Biologi dan Pembelajarannya, 2022)
Pteridophyta is one of difficult submaterial to understand by students during the learning process. It’s caused by the limitation of  supporting facilities such as media or teaching materials. Module could make students learning independently with or without guidance of teacher. This study aims to determine the feasibility of the module in the sub-material of ferns for class X SMA. The module of  the fern sub-material has been made based on the results of the Pteridophyta inventory in the Gunung Belungai Protected Forest, Sanggau Regency, in March-April 2021. The validity of the module teaching materials is calculated based on the Lawshe method. The validation of the fern module teaching materials was carried out by 5 validators consisting of 2 Biology Education lecturers and 3 Biology subject teachers. Based on the results of data analysis from the five validators, the validity  for each criteria are 3 (good) and 4 (very good) so the module of teaching materials get a CVR 0.99 and CVI 1. Module of submaterial of fern are valid and feasible to used as learning media.